THE INFLUENCE OF ZAKAT MAL EXPENDITURE TOWARDS HUMAN RESOURCES PERFORMANCE THROUGH THE ALTRUISM AND THE QUALITY OF WORK LIFE (Case Study in Universitas Islam Sultan Agung Semarang) - Putra Anugrah Satria (IJIBE (International Journal of Islamic Business Ethics), 2018)
This study aims to analyze the effect of zakat mal expenditure on  the performance of human resources for lecturers at Sultan Agung Semarang  Islamic  University with Altruism    and Quality of Work Life as an intervening variable. The population in this study were lecturers at Sultan Agung Islamic University Semarang. The sampling technique using convenience sampling method and purposive sampling. Samples taken were 223 respondents.The research method used was explanatory research with a quantitative approach because it explained the relationship between variables using questionnaires as a tool in data collection to reveal data on zakat mal expenditures, human  resource  performance with Altruism and Quality of Work Life as intervening. The analysis technique used in this study is linear regression analysis using SPSS version 23.0 for Windows software tools.The results of this study indicate that the expenditure of zakat mal, Altruism and Quality of Work Life has a positive and significant effect on the performance of human resources.keywords: Effect of Spending on Zakat, Altruism , Quality of Work Life , Human Resource Performance